Pengaruh Model Pembelajaran Discovery Learning Versus Direct Instruction Dan Motivasi Belajar Terhadap Hasil Belajar Fisika Siswa SMA - Ani Irawati; Rufi’i Rufi’i; I Wayan Arsana (UMSU, 2023)
Current education required to be able to have the competencies that have been proposed. Learning in the 21st century requires students to play an active role and think critically. The government's effort to realize this is by changing the curriculum, namely the independent curriculum. The aim of the independent curriculum is to create fun education for students and teachers and also to develop students' potential. Methods of data collection using questionnaires and written tests. In testing. The data collection method for learning motivation uses a questionnaire, while for the learning achievement test uses a test score document. To test the hypothesis used a statistical test using two-way ANOVA with the help of SPSS. Before carrying out the two-way analysis test, a parametric conditional test was carried out. From a series of tests carried out, namely instrument testing, hypothesis testing, and analysis, the research instruments and data met the required statistical test requirements.The results of this study indicate: (1) there are differences in physics learning outcomes between groups of students who are treated using the Discovery Learning learning model and groups of students using the Direct Instruction learning model for class X students of SMAN 1 Sukodadi, (2 there are differences in physics learning outcomes between groups of students who have high learning motivation and low learning motivation in class X SMAN 1 Sukodadi, (3 there is an interaction between learning models and learning motivation on physics learning outcomes in class X SMAN 1 Sukodadi.